Oleo cocos - Zuraidi, Afiq Syahmi; Musa, Nur Hasyimah Jamrah; Md Arsad, Nurul Izzati Khairunnisa; Ismail, Salwani; Mat Rosid, Salmiah Jamal; Othman, Muhammad Zamir; Nasir, Nur Atiqah (Pusat Asasi, UiTM Cawangan Dengkil, 2020)
Some people tend to pour the used grease and cooking oil directly down to their kitchen sink drain. These things will accumulate inside the drain pipes, which caused a plumbing problem. When the grease and oil interact with water, it will coagulate and attaches itself to the interior of pipes. Over time, the deposits can restrict water flow and eventually clog the drain that will block the entire pipe system and could lead to the water overflowing out of the sink. Regarding this problem, superhydrophobic and superoleophilic materials such as modified raw cotton, natural fiber material, organic adsorbent and nanotubes have a significant role in treating the oil spillage. Activated carbon is one of the organic sorbents used as an absorber to trap oil spills due to its high surface area, low density, good chemical stability and environmental friendliness. Therefore, an invention named ‘ Oleo cocos’ is introduced as the solution to this problem. In this study, the activated carbon was formed from waste coconut shells by carbonisation process and ground to powder form. The powder was then tested for the adsorption efficiency in a simulated drainage system. The activated carbon from coconut shells has demonstrated an effective adsorption capacity. Thus, this product can be used by the community for daily routine to prevent the clog in the kitchen sink which can reduce the cost for plumbing maintenance. Thus, this product is a new invention to solve the problem in our community by using household waste.